METODE DAKWAH MELALUI AL-QUR’AN DI PONDOK YANBU’UL QUR’AN KUDUS - Ahmad Ainun Najib; Ahmad Fauz (ASWALALITA: Journal of Da'wah Management, 2023)
Learning the Qur'an involves learning how to read it, translate it, and understand the rulings, lessons, and instructions it contains. Likewise, teaching the Qur'an includes efforts to guide and guide people in reading, translating and understanding the content of the verses of the Qur'an. By using a qualitative method, and collecting data from literature sources which include primary and secondary sources. The collection of literature data is carried out through a search for the theme of the theoretical basis, and analysis of research models on the Qur'an, there is tafsir, asbabun nuzul, akhlaq and qira'ah sab'ah which are guaranteed sanad to rhythm, there is a complexity in understanding and studying the Qur'an as a provision for plunging in the world of society, especially for those of us who capitalise on the Qur'an translation alone makes a whip for us as people of Islam.